Lignin depolymerization into aromatic monomers over solid acid catalysts - Deepa, Ayillath K.; Dhepe, Paresh Laxmikant (ACS Catalysis, 2015)
It is imperative to develop an efficient and environmentally benign pathway to valorize profusely available lignin, a component of nonedible lignocellulosic materials, into value-added aromatic monomers, which can be used as fuel additives and platform chemicals. To convert lignin, earlier studies used mineral bases (NaOH, CsOH) or supported metal catalysts (Pt, Ru, Pd, Ni on C, SiO2, Al2O3, etc.) under a hydrogen atmosphere, but these methods face several drawbacks such as corrosion, difficulty in catalyst recovery, sintering of metals, loss of activity, etc. Here we show that under an inert atmosphere various solid acid catalysts can efficiently convert six different types of lignins into value-added aromatic monomers. In particular, the SiO2Al2O3 catalyst gave exceptionally high yields of ca. 60% for organic solvent soluble extracted products with 95 +/- 10% mass balance in the depolymerization of dealkaline lignin, bagasse lignin, and ORG and EORG lignins at 250 degrees C within 30 min. GC, GC-MS, HPLC, LC-MS, and GPC analysis of organic solvent soluble extracted products confirmed the formation of aromatic monomers with ca. 90% selectivity. In the products, confirmation of retention of aromatic nature as present in lignin and the appearance of several functional groups has been carried out by FT-IR and H-1 and C-13 NMR studies. Further, isolation of major products by column chromatography was carried out to obtain aromatic monomers in pure form and their characterization by NMR is presented. A detailed characterization of six different types of lignins obtained from various sources helped in substantiating the catalytic results obtained in these reactions. A meticulous study on fresh and spent catalysts revealed that the amorphous catalysts are preferred to obtain reproducible catalytic results.
Keywords: aromatic monomers; Biomass; column chromatography; depolymerization; lignin; solid acid catalysts

Formic-acid-induced using recyclable-ionic liquids as catalysts for lignin conversion into aromatic co-products - Singh, Sandip K.; Dhepe, Paresh L. (Waste and Biomass Valorization, 2019)
Lignin has been widely named as a sustainable and renewable bioresource of energy, fuels, chemicals and materials, particularly phenolic chemicals production on Earth. These bio-derived compounds are in great potential need of biorefinery to valorize complete plant biomass. Lignin depolymerization showed a great promise approach to convert into low molecular aromatic products. In this report, high molecular weight (54,000 Da) lignin depolymerization into maximum yields (87%), (>= 95 +/- 6% mass balance) using a formic acid along with dual (-SO3H) functionalized imidazole-based recyclable (4 times) Bronsted acidic ionic liquids (BAILs) as catalysts have been investigated in H2O-CH3OH (1:5, v/v) at 120 degrees C for 1 h. The structural correlations between the lignin and aromatic products were studied by bulk (CHNS, GPC, etc.) and molecular (UV-Vis, FT-IR, NMR (1D/2D) levels experimental techniques. Additionally, the identification of aromatic products was carried out by applying HPLC, GC and GC-MS techniques. Graphic Addition of a formic acid into Bronsted acidic ionic liquids improved the catalytic efficiency significantly for lignin depolymerization into 87% low molecular weight aromatic products. [GRAPHICS] .
Keywords: Bulk and molecular levels analysis; depolymerization; Dual functionalized ionic liquids; Formic acid; lignin

Copper/Iron cocatalyzed depolymerization of postconsumer polycarbonate: a one-pot strategy to synthesize aryl ethers - Moyilla, Nageswararao; Padhi, Ganeshdev; Kalsi, Deepti; Barsu, Nagaraju (ACS SUSTAINABLE CHEMISTRY & ENGINEERING, 2024)
Keywords: aryl ethers; copper/iron cocatalysis; depolymerization; polycarbonates; Value-added products

Iron in organometallic transformations: a sustainable substitute for noble metals - Kumar, Rohit; Tewari, Tanuja; Chikkali, Samir H. (ChemCatChem, 2024)
Transition metal catalysis plays a pivotal role in chemical synthesis. Noble metals often grab significant attention in organometallic catalysis due to their high reactivity. However, the serious issues associated with these metals such as low abundance, toxicity, geopolitical limitations, and volatile prices are driving the scientific community to discover sustainable alternatives. In this context, iron appears to be the first choice as an alternative metal due to its unique properties, including a range of stable oxidation states, Lewis acidity, high abundance in the earth's crust, and low toxicity. Over the past two decades, substantial progress has been made in iron catalysis. This overview examines the recent developments in iron-catalyzed industrially relevant transformations such as hydroformylation, olefin isomerization, hydrosilylation, hydrophosphination, carbonylation, Wacker-type oxidation, and plastic depolymerization. As witnessed throughout this review, the performance of iron can be significantly altered by suitable ligand selection and by tailoring the electronic and steric properties of the iron center. While noble metals remain the industry work-horse, iron is inching closer and with extensive scientific understanding, it may replace noble metals in the near future. Late transition metals catalyze several reactions and have been the industry work-horse for decades. While, earth abundant metals are rarely used in industrially relevant transformations. In this overview, we examine the recent development in iron-catalyzed industrially relevant reactions such as hydroformylation, olefin isomerization, hydrosilylation, hydrophosphination, carbonylation, Wacker-type oxidation, and plastic depolymerization. Iron is inching closer and may replace noble metals in near future. image
Keywords: Alkene Isomerization; alkyne; Carbonylation; depolymerization; Hydrophosphination; Hydrosilylation; iron catalysis

Depolymerization of waste polycarbonates to value-added products - Padhi, Ganeshdev; Pansare, Vaibhav Ramachandra; Bajpai, Priyam; Krishna, Gamidi Rama; Vanka, Kumar; Barsu, Nagaraju (ChemSusChem, 2025)
Additive free aminolysis method developed for the depolymerization/upcycling of polycarbonates. We report here chemical recycling of polycarbonate under ambient conditions to get its monomer bisphenol A, monoaminocarbamate and biscarbamates in 1 : 2 : 1 ratio respectively. By employing the secondary amine as the aminating reagent, facilitates the depolymerization to work under additive/catalyst free conditions. The developed method deals with depolymerization of waste polycarbonates and works even with late-stage amine derivatives such as amoxapine and desloratadine which are drugs molecules known to treat neurotic disorders and allergies respectively. The reaction can be scaled up and works with similar efficacy which depicts the efficiency of the depolymerization of wasteend-of-life polycarbonate plastic waste. The biscarbamate and bisphenol-A was further subjected for the post functionalization to obtain amides and phenol in good yields. Developed additive/catalyst free aminolysis of waste polycarbonates to carbamates and monomer BPA at ambient conditions. Variety of secondary amines were screened including the late stage amine derivatives like amoxapine and desloratadine which delivered the expected products successfully. Later the developed methodology was even applied for the different end-of-life polycarbonates with the secondary amine and achieved the depolymerization without any obstacle. Further carried out the scale up reaction and derivatization of carbamates and BPA to amide and phenol synthesis. image
Keywords: Aminolysis; carbamates; depolymerization; End-of-life; Polycarbonate

Waste polyethylene to long-chain unsaturated esters and alcohols via alkene cross-metathesis - Khopade, K. V.; Bodkhe, D. V.; Chikkali, S. H. (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2025)
The conversion of waste polyethylene into valuable long-chain functional molecules offers a contemporary solution to the global plastic waste challenge. This study presents a two-step catalytic approach, comprising of polyethylene (PE) dehydrogenation followed by cross-metathesis with renewable resource-derived functional olefins, catalyzed by the Grubbs-II catalyst (G-II). A dehydrogenated polyethylene (DHP) was subjected to a tandem catalytic cross-alkene metathesis with functional olefins under mild conditions to achieve approximately 36% conversion of DHP into valuable long-chain building blocks with controlled product distribution. Comprehensive characterization of intermediates and products was performed using NMR, GC, GC-MS, GPC, and DSC. In the alkene cross-metathesis with methyl-10-undecenoate, the product distribution consisted of 23% lower alkenes (C8-C14), 40% unsaturated long-chain mono-esters (C12-C18), and 37% unsaturated di-esters. In the case of 10-undecen-1-ol, the distribution included 20% lower alkenes (C8-C11), 32% unsaturated long-chain (C12-C18) mono-alcohols, and 48% unsaturated di-alcohols. This strategy opens up new opportunities for converting waste polyethylene into high-value chemical intermediates, enabling resource recovery and delivering environmental benefits.
Keywords: depolymerization; functional olefins; Metathesis; Recycling; Value-added products